2019
DOI: 10.1111/psyp.13506
|View full text |Cite
|
Sign up to set email alerts
|

The mindful attention and awareness scale is associated with lower levels of high‐frequency heart rate variability in a laboratory context

Abstract: Trait mindfulness has been associated with well‐being. A key component of trait mindfulness is intentional attention and awareness which is most commonly measured by the Mindful Attention and Awareness Scale (MAAS). This study investigated the relationship between the MAAS and cardiovascular (HF‐HRV, heart rate) reactivity to two laboratory stressors that evoked different patterns of change in heart rate (HR). One stressor (viewing a video of a surgery) evoked HR deceleration while the other stressor (mental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
1
14
1
Order By: Relevance
“…People differ in how mindful they inherently are. This so-called 'trait' mindfulness is most commonly measured by the MAAS [23]. Higher trait mindfulness is associated with better psychological and physical health, resilience, optimism, fulfilment, self-esteem, autonomy, and competence [4,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People differ in how mindful they inherently are. This so-called 'trait' mindfulness is most commonly measured by the MAAS [23]. Higher trait mindfulness is associated with better psychological and physical health, resilience, optimism, fulfilment, self-esteem, autonomy, and competence [4,24].…”
Section: Discussionmentioning
confidence: 99%
“…Higher trait mindfulness is associated with better psychological and physical health, resilience, optimism, fulfilment, self-esteem, autonomy, and competence [4,24]. Lower trait mindfulness is associated with neuroticism, negative affect, anxiety, depression, self-consciousness, rumination, and experiential avoidance [4,23]. Regular meditation is associated with an improved MAAS score, particularly if it is carried over into daily life [4].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, for example, an inverse relationship was found between mindful awareness and parasympathetic activation, which the authors believe to be linked to laboratory-related aspects such as higher vigilance, higher cognitive load, etc. (Watford et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, compelling evidence indicates that meditative practices have the potential to facilitate handling negative thoughts and emotions, induce a state of calmness and presence, and increase the activity of the vagal nerve [38,39]. In a recent laboratory experiment conducted by Koerten and colleagues [12,40], the authors investigated the effects of mindfulness, with a focus on nonjudgment, on recovery from stress in perfectionists. In the aforementioned experiment, the authors made use of heart rate variability analysis to further understand the impact of brief mindfulness meditation on cardiovascular responses.…”
Section: Effects Of Meditative Practices On Cardiovascular Healthmentioning
confidence: 99%